Covalent Attachment of Active Enzymes to Upconversion Phosphors Allows Ratiometric Detection of Substrates. Issue 65 (16th October 2020) - Burgess, Letitia; Wilson, Hannah; Jones, Alex R.; Harvey, Peter; Natrajan, Louise S.; Hay, Sam
Abstract: Upconverting phosphors (UCPs) convert multiple low energy photons into higher energy emission via the process of photon upconversion and offer an attractive alternative to organic fluorophores for use as luminescent probes. Here, UCPs were capped with functionalized silica in order to provide a surface to covalently conjugate proteins with surface‐accessible cysteines. Variants of green fluorescent protein (GFP) and the flavoenzyme pentaerythritol tetranitrate reductase (PETNR) were then attached via maleimide‐thiol coupling in order to allow energy transfer from the UCP to the GFP or flavin cofactor of PETNR, respectively. PETNR retains its activity when coupled to the UCPs, which allows reversible detection of enzyme substrates via ratiometric sensing of the enzyme redox state. Abstract : Variants of GFP and the flavoenzyme PETNR were attached to upconverting phosphors (UCPs) via maleimide‐thiol coupling in order to allow apparent energy transfer from the UCP to the cofactors of GFP or PETNR. PETNR retains its activity when coupled to the UCPs, which allows reversible detection of enzyme substrates via ratiometric sensing of the enzyme redox state.